Chinese News Discourse From Perspectives of Communication, Linguistics and Pedagogy - liu, nancy xiuzhi; VEECOCK, Candace; Zhang, Shixin Ivy (Taylor & Francis, 2021)
As a country in transition, Chinese news discourse has quite distinctive characteristics, and more so given the power of state media in society. With China's engagement in world affairs and its massive Belt and Road Initiative (BRI) now in place, Western media coverage of China has dramatically increased. Against this backdrop, news dissemination and discourse demonstrate a need for academia to give perspectives with interdisciplinary approaches. Chinese News Discourse presents original research from academics in China and the West, showing theoretical, methodological and practical dimensions between news media and discourse. The book focuses on Chinese news discourse by examining what new modern features it demonstrates in contrast and comparison to news discourses in other countries in the coverage of such hot topics as the BRI or the 70th Anniversary of the Founding of the People's Republic of China, just to name a few. This book is a useful resource for scholars and students of discourse, language, media and communication studies, as well as translation studies.